Development of Embroidery Design Skills Program for Children with Hearing Impairment - Putri, Syabila; Aprilia, Imas Diana (Department of Special Education, 2023)
Vocational education is also often referred to as skills. One of them is fashion skills, which is a discipline and art regarding the application of aesthetic design, and natural beauty to clothing and its additional decoration. This research aims to create a program on learning fashion skills in embroidery design for teachers and students with hearing impairments. The approach used in this research is research and development with exploratory mixed method research design and at the program trial stage researchers use experimental methods with single subject research design (A-B-A). The results of a good learning program trial lead students to have a good learning experience, the program that has been made shows that the program can be useful and useful, especially for students. The results of this study are expected to be taken into consideration for teachers in providing learning fashion skills in embroidery design to students.